The carB Gene of Escherichia coli BL21(DE3) is Associated with Nematicidal Activity against the Root-Knot Nematode Meloidogyne javanica - Xia, Yanfei (Pathogens, 2021)
Biological nematicides have been widely used to lower the losses generated by phytoparasitic nematodes. The purpose of this study was to evaluate the nematicidal effects of Escherichia coli BL21(DE3) against Meloidogyne javanica and to identify nematicide-related genes. Culture filtrates of BL21(DE3) caused juvenile mortality and inhibited egg hatching in a dose-dependent manner. In the greenhouse, treatment of tomato seedlings with BL21(DE3) culture filtrates at 50 and 100% concentrations not only reduced the amount of M. javanica egg masses and galls, but improved plant root and shoot fresh weight. Culture filtrate analysis indicated that the nematicidal active ingredients of strain BL21(DE3) were non-proteinaceous, heat and cold resistant, sensitive to pH and volatile. To identify the genes associated with nematicidal activity, a BL21(DE3) library of 5000 mutants was produced using Tn5 transposase insertion. The culture filtrate of the MB12 mutant showed no nematicidal activity after 72 h of treatment and thermal asymmetrical interlaced PCR demonstrated that the carB gene was disrupted. Nematicidal activity was restored when the pH of the MB12 culture filtrate was adjusted to the original pH value (4.15) or following MB12 complementation with the carB gene, confirming a role for carB in mediating pH value and nematicidal activity. The outcomes of this pilot study indicate that BL21(DE3) is a potential microorganism for the continuable biological control of root-knot nematode in tomato and that carB affects the nematicidal activity of BL21(DE3) by modulating the pH environment.